Role of first trimester screening test in predicting the perinatal outcomes in low risk term pregnancies - Gökçe Turan; Ezgi Turgut; Halis Özdemir; Roujin Akbarihamed; Sibel Konca; Deniz Karcaaltıncaba; Merih Bayram (Perinatal Medicine Foundation, 2022)
Objective: This study aims to investigate the relationship between the nuchal translucency (NT) values measured in the first trimester and the well-being of the newborn. Methods: The study was planned as a retrospective cross-sectional study and was conducted between January 2018 and January 2020. A total of 2394 patients who had a combined test and delivered at our university hospital were included in the study. The demographic data of the pregnant women were recorded. NT MoM values, PAPP-A and β-hCG MoM values, birth weight, gender, need for neonatal intensive care (NICU), and Apgar scores were evaluated. Results: It was found that NT (MoM) values were similar among the SGA, AGA, and LGA groups (p=0.159). PAPP-A (MoM) values were similar in the SGA group compared to AGA and LGA infant groups (p=0.947). It was also found that β-hCG (MoM) values were similar in the AGA group compared to SGA and the LGA infant groups (p=0.694). When compared with those with NICU and non-NICU, the NT, PAPP-A, β-hCG, and birth weight values were again not found to be statistically significant (p>0.05). The NT, PAPP-A, β-hCG, and male gender factors were evaluated in the Binary Logistic Regression Analysis, in which being an SGA baby was considered as a risk. It was found that a 1 mm increase in NT values increased the risk of having an SGA baby 2.63 times at a statistically significant level (OR=2.636, p=0.009, 95% CI: 1.277-5.440). PAPP-A, β-hCG levels, and having a male gender were not related to the risk of having an SGA baby. Furthermore, NT, PAPP-A, β-hCG levels, and having a male gender were not associated with the risk of NICU hospitalization. Conclusion: In conclusion, we could not predict the birth weight with increased NT MoM values that were detected in the first trimester combined test in this study; however, we found that the risk of having an SGA fetus increases with a weak rise in NT value.